La médiatisation de soi et la constitution des sujets - Gloria Awad (Communication)
Self-mediatization is not limited to modern times, where it is experiencing a generalized intensification whose foundation is made to allow the experience to take form, to be something else than an heterogeneous package, a bundle of sensations. Using sociohistorical approach the author examines the relationship between “techniques of self” and the new basis of identity. Self-mediatization appears as the configuration of experience in all available forms of crystallization. These forms are embedded in communicational objects that give experience a specific, autonomous existence while creating a complex relationship with the subject who is thus affected.